Analisis Perubahan Iklim Serta Dampaknya pada Masyarakat Petani Padi Sawah - La Harudu; Sitti Kasmiati; Andrias Andrias; La Ode Nursalam (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2025)
Climate change, driven by global warming, has triggered the occurrence of El Niño and La Niña phenomena and prolonged rainy and dry seasons. These changes have significantly impacted farmers, fishers, and human activities across various sectors. According to research findings, annual air temperature has shown variability, ranging from moderate to very good categories. However, in 2021, a notable decline was recorded, with temperatures categorized as very poor. In contrast, annual humidity levels generally remained within the moderate to very good range, except in 2020 when humidity was categorized as very poor, despite temperature conditions that year being moderate for 8 months and very good for 4 months. Wind speed from 2019 to 2023 consistently showed a very good trend. Based on the comparison between the average number of dry and wet months, the climate typeaccording to the Schmidt-Ferguson classification—shifted from type C to B, then B to B, B to A, and finally A to C, resulting in a climate sequence of C–B–B–A–C over the observed period. Interestingly, these climate changes have not had a significant impact on the income levels of paddy farmers in Baruga Village. This resilience is largely due to the village's geographical features, which include surrounding mountains and hills as well as the flow of the Konawe River, all of which contribute to a stable water supply and support sustainable agricultural productivity.